Multiple Positive Sweat Chloride Tests in an Infant Asymptomatic for Cystic Fibrosis - Cotten, Steven W.; Bender, Laura M.; Willis, Monte S. (Laboratory medicine, 2012)
[...]one study reported that the percentage of infants diagnosed with CF increased with increasing IRT values (CF diagnosed in 1.6% of infants with IRT values <100 ng/mL, and in 48% of infants with IRT values >150 ng/mL).14 However, circulating trypsinogen levels cannot be used as a screening test for CF in all age groups. Positive cultures or acquisition of Pseudomonas aeruginosa infection should be treated with anti-pseudomonal antibiotics and increased airway clearance even in the absence of symptoms.25 For evaluation of pulmonary function, the CF foundation recommends a baseline chest x-ray be obtained within the first 3-6 months of life and once again within the first 2 years of life in the presence or absence of symptoms.25 Patient Follow-Up and Treatment In addition to salt supplementation, the patient was started on a regimen of CF multivitamins and pancreatic enzyme supplementation (one-half capsule with feedings).